The inquiry investigation group learning model: Improving students’ critical thinking skills, cognitive learning outcomes, and scientific attitudes - Mery Pattipeilohy; Dominggus Rumahlatu; Sriyanti, I. A Salmanu; Kristin Sangur (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
Innovative learning is carried out through a combination of the Investigation Group (IG) and Inquiry Strategy (IS) into a modified learning model namely IIG (Inquiry Investigation Group). This study analyzes the effect of the IIG model on critical thinking, cognitive learning outcomes, and scientific attitudes on Class XI High School students in West Seram Regency. The sample was 102 students, and the data was analyzed using inferential statistics namely covariance analysis (ANCOVA). The results show that the IIG model has an effect on critical thinking (0.000<p=0.05), cognitive learning outcomes (0.000<p=0.05), and students’ scientific attitudes (0.000<p=0.05). This indicated that IIG consists of learning stages of orientation, conceptualization, investigation, report generation, and discussion-evaluation. The finding of the research recommends the application of the IIG model in learning other biology concepts in high school. In addition, this research can contribute to providing innovation in biology learning in the era of society 5.0.